Aplikasi Konsep Trilogy Of Beauty pada WF Skin Care Clinic di Surabaya - Dessy Natalia; Stephanus P Honggowidjaja (Intra, 2014)
WF skin care clinic is a facility that provides health and beauty skin treatment. Curretly WF provides many facilities to offers. However, that facilities haven’t supported well by the organizations of comfortable room circulation. This project aims to provide a complete service of skin care facility, by creating an effective and efficient atmosphere for clinical, space especialy for medical and non medical service, as well as a clear spatial separation between men and women to create flexibility activities.